Subaru disables Starlink in Mass. new cars amid right-to-repair fray; Debate lingers over updated law, expanded data access - Vellequette, Larry P (Automotive News, 2021)
Subaru of America has disabled its Starlink telematics subscription service on all new 2022 vehicles sold or housed in Massachusetts so it doesn't violate an amended right-to-repair law that is the subject of a dispute in federal court between the state and the Alliance for Automotive Innovation. The data platform that the new law requires to provide the data does not exist and will not exist any time soon. [...]a time as that platform can be developed, and Subaru can redesign its telematics hardware and software to comply with the new law's requirements, we feel that this is our only option." [...]on Oct. 22, Massachusetts Attorney General Maura Healey filed a motion seeking to introduce Subaru's blocking of Starlink as evidence in the case, arguing that it contradicted claims by the alliance on behalf of its members that disabling telematics systems such as Starlink or General Motors' OnStar was a "practical impossibility."